Teachers’ Support and Pupils’ Writing Strategies in a Networked Elementary-School Learning Environment Integrating a Blog - Thériault, Pascale; Allaire, Stéphane; Gagnon, Vincent (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
Although the affective dimension of writing is important and well documented, we know less about how teachers and students are making use of the blog in classrooms to advance specifically cognitive goals connected to writing. It is with this in mind that a case study was carried out to closely document the effect of classroom blogs on the development of writing in 6th grade pupils. The study intended to a) describe the kind of support about writing provided by teachers and b) describe how writing strategies and processes were used by the pupils while they were using the blog. Two teachers and the students in their classrooms participated in our study. Data were collected from classroom observations and interviews. We used Hayes and Flower’s writing processes, elaborated in 27 writing strategies, to analyze the classroom data. The results reveal that teachers focused the most on planning and revising processes.